2016
DOI: 10.5194/soil-2-147-2016
|View full text |Cite
|
Sign up to set email alerts
|

Organic wastes from bioenergy and ecological sanitation as a soil fertility improver: a field experiment in a tropical Andosol

Abstract: Abstract. Andosols require the regular application of phosphorus (P) to sustain crop productivity. On an Andosol in NW Tanzania, we studied the short-term effects of amending standard compost, biogas slurry and CaSa compost (containing biochar and sanitized human excreta) on (i) the soil's physico-chemical properties, on (ii) biomass growth and crop productivity, and on (iii) the plants' nutrient status. The practice-oriented experiment design included the intercropping of seven locally grown crop species plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…In addition, [93] found that application rates of >25 kg·P·ha −1 ·season −1 over the course of four seasons were capable of replenishing levels of P in a P deficient soil in Western Kenya. In contrast, the application of 40 or 70 kg·P·ha −1 in the form of biogas slurry or standard compost, respectively, was not sufficient to increase extractable soil P, as demonstrated in a short-term field trial on the local Andosol [61]. Adding about 140 kg·P·ha −1 with CaSa-compost, however, significantly increased levels of available P in the soil after the experiment, and thus, immediately contributed to mitigating P deficiency [17].…”
Section: Sustainability Aspects Of Intersectional Resource Managementmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, [93] found that application rates of >25 kg·P·ha −1 ·season −1 over the course of four seasons were capable of replenishing levels of P in a P deficient soil in Western Kenya. In contrast, the application of 40 or 70 kg·P·ha −1 in the form of biogas slurry or standard compost, respectively, was not sufficient to increase extractable soil P, as demonstrated in a short-term field trial on the local Andosol [61]. Adding about 140 kg·P·ha −1 with CaSa-compost, however, significantly increased levels of available P in the soil after the experiment, and thus, immediately contributed to mitigating P deficiency [17].…”
Section: Sustainability Aspects Of Intersectional Resource Managementmentioning
confidence: 94%
“…In prior studies focusing on a household level, we already introduced [39], demonstrated [61], and analyzed, in detail, the recycling potentials of an intersectional resource management for the example of smallholdings in Karagwe, TZ [41]. In the present work focusing on a farm level, we systematically compare specific approaches to recover residues as resources for IPNM, such as biogas slurry, urine, or co-composted human faeces, and biochar.…”
Section: Research Objectives and Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conserving the soil feature can deliver economic gain in more competent use of nutrients and insecticides, growth in yield, enhancements in quality of water and air (USDA-ERS, 1997). The application of organic matter to the soils providing nutrients to the plants and playing a key role in the soil's water holding capacity, its porosity and water infiltration rate (Krause et al, 2016;Yazdanpanah et al, 2016). The properties of dry soil along with its type have a great importance in agriculture (Ahire et al, 2013).…”
Section: Introductionmentioning
confidence: 99%